Matriarchal associations and reproduction in a remnant subpopulation of desert-dwelling elephants in Namibia - Keith Leggett; Laura Brown; Rob Ramey (Pachyderm)
This study focused on a subpopulation of desert-dwelling elephants in the Kunene region of north-western Namibia, where rainfall and resources are scarce, and the rate of reproduction and recruitment is low. This subpopulation can be considered a remnant; its oldest members are survivors of the war-related poaching that occurred in the region during the 1970s and 1980s, and its numbers have still not recovered to pre-war levels. Unlike less disturbed elephant populations with strong, multi-tiered matrilineal associations, previous research suggested that the associations in the Kunene subpopulation involved only loose affiliations lacking strong social bonds. Taking that study a step further, this manuscript examines the social structure of all adult females (n=14) in the subpopulation, based on observational data combined with mitochondrial DNA (mtDNA) sequence data. A network analysis was generated from nearly eight years of association data. It was found that female desert-dwelling elephants live in first-tier/family units or small second-tier/family groups, and in at least two cases these include unrelated adult females. Associations at the level of third-tier/bond groups are rare and transitory, and there was no evidence of these being dominated by a single female or matriarch. The matrilineal social structure in this subpopulation is consistent with reports from other poached or culled elephant populations in Africa. Collectively, the results of these studies are inconsistent with the classic model of elephant social structure—stable, strictly matrilineal societies—especially in cases where poaching or culling has occurred, even if it transpired decades previously.